Investigation of the nutritional attitudes and behaviors of the adolescents of the age group of 16-18 who are engaged in sports and the ones who do not - Akil, Mustafa; Top, Elif; Yildiz, Serkan (Progress in Nutrition, 2019)
The present study was conducted to determine the nutrition exercise attitudes and nutrition exercise behaviors of adolescents the age group of 16-18 who actively perform sport activities and the ones who do not. The study was conducted on a study group comprised of 174 female (44.2%) and 220 male (55.8%) participants; totaling to 394 subjects. In terms of the gender distribution of the participating adolescents, while there is no significant difference between them based on the nutrition exercise behaviors scale, male adolescents displayed significant difference in the sub-factors of healthy nutrition, unhealthy nutrition and meal order in the nutrition exercise behaviors scale compared to the females (p<0.05). Furthermore, it was also determined that nutrition exercise attitudes of adolescents who actively performed sport activities were more positive compared to the ones who do not; and this difference was with the healthy nutrition behaviors and meal order; and that adolescents who succeeded to rank in sport competitions had more positive healthy nutrition behavior and meal order behaviors compared to the one who do not (p<0.05). Consequently, it can be said that the factor of gender affects the food and exercise attitudes and behaviors of the adolescents of the 16-18 age group; the food and exercise attitudes of the ones who are engaged in sports is more positive compared to the ones who are not, and the children who rank in sports are more attentive to their healthy feeding and the regularity of their meals.